Intravenous Treatment with a Long-Chain Omega-3 Lipid Emulsion Provides Neuroprotection in a Murine Model of Ischemic Stroke A Pilot Study - Berressem, Dirk; Koch, Konrad; Franke, Nicole; Klein, Jochen; Eckert, Gunter P.; Justus Liebig University Giessen (My University, 2016)
Single long-chain omega-3 fatty acids (e.g. docosahexaenoic acid (DHA) or eicosapentaenoic acid (EPA)) are known for their neuroprotective properties associated with ischemic stroke. This pilot study aimed to test the effectiveness of an acute treatment with a long-chain omega-3 lipid emulsion (Omegaven 10%®, OGV) that contains fish oil (DHA 18 mg/ml; EPA 21 mg/ml) and a-tocopherol (0.2 mg/ml) in a transient middle cerebral artery occlusion (MCAO) model of ischemic stroke in mice. For this purpose, female CD-1 mice were anesthetized and subjected to 90 minutes of MCAO. To reflect a clinically relevant situation for an acute treatment, either after induction of stroke or after reperfusion, a single dose of OGV was injected intravenously into the tail vein (5 ml/kg b.w.). A neurological severity score was used to assess motor function and neurological outcome. Stroke-related parameters were determined 24 hours after MCAO. Microdialysis was used to collect samples from extracellular space of the striatum. Mitochondrial function was determined in isolated mitochondria or dissociated brain cells. Inflammation markers were measured in brain homogenate. According to control experiments, neuroprotective effects could be attributed to the long-chain omega-3 content of the emulsion. Intravenous injection of OGV reduced size and severity of stroke, restored mitochondrial function, and prevented excitotoxic glutamate release. Increases of pro-inflammatory markers (COX-2 and IL-6) were attenuated. Neurological severity scoring and neurochemical data demonstrated that acute OGV treatment shortly after induction of stroke was most efficient and able to improve short-term neurological outcome, reflecting the importance of an acute treatment to improve the outcome. Summarising, acute treatment of stroke with a single intravenous dose of OGV provided strong neuroprotective effects and was most effective when given immediately after onset of ischemia. As OGV is an approved fishoil emulsion for parenteral nutrition in humans, our results may provide first translational data for a possible early management of ischemic stroke with administration of OGV to prevent further brain damage.
Keywords: ddc:610